Heart like a Fakir General Sir James Abbott and the fall of the East India Company - Mason, M. Chris (Rowman & Littlefield, 2023)
"This book explores the last years of the British East India Company using the life of General Sir James Abbott-explorer, guerilla, district officer, and possible inspiration for Mr. Kurtz in Heart of Darkness-as a thread to reexamine the social and sexual relationships between Britons and Indians and chronicle the collapse of their social contract"--
Keywords: Abbott, James -- 1807-1896; East India Company -- London; Abbott, James / Sir / 1807-1896; East India Company / Army / Officers / Biography; British / India / Social life and customs / 19th century; India / History / Sepoy Rebellion, 1857-1858 / Causes; East India Company / History / 19th century; East India Company; East India Company / Army; Armed Forces / Officers; British / Social life and customs; War / Causes; India; 1800-1899; Biographies; History